The relationship between parent–young adult religious concord and depression. Issue 1 (2nd January 2020) - Gwin, Shannon; Branscum, Paul; Taylor, Laurette; Cheney, Marshall; Maness, Sarah B.; Frey, Melissa; Zhang, Ying
ABSTRACT: The study's purpose was to evaluate the relationship between depressive symptoms in emerging adults (ages 18–24) and religious concordance/discordance with their parents (n = 161 dyads). Online surveys were distributed to young adults and a corresponding parent, evaluating religiosity, depressive symptoms (young adults only), and demographics. Regarding depressive symptoms among surveyed young adults, concordance for non-organizational religiosity (e.g., prayer/meditation; p = .005), and mother-young adult concordance were significantly inversely related (p = 0.0015), females (p = 0.001) were more likely to report depressive symptoms than males, and young adults with parental relationship asset (one parent: p = 0.0048; both parents: p = 0.0002) reported significantly lower depressive symptoms. Recommendations are discussed.